2015
DOI: 10.1002/ece3.1538
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring variation in tadpole morphology and performance linked to predator regime

Abstract: Divergent natural selection drives a considerable amount of the phenotypic and genetic variation observed in natural populations. For example, variation in the predator community can generate conflicting selection on behavioral, life-history, morphological, and performance traits. Differences in predator regime can subsequently increase phenotypic and genetic variations in the population and result in the evolution of reproductive barriers (ecological speciation) or phenotypic plasticity. We evaluated morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 96 publications
1
27
1
1
Order By: Relevance
“…Therefore, individuals could display larger and rounded mouth, more propulsion and/or maneuverability but lower endurance (dorso-ventral flexion) along the increasing of PC1 values. PC2 was principally driven by functional traits related to locomotion, indicated that with increased PC2 values, individuals were more compact and rounded, but less propulsion and/or maneuverability (i.e., lower movement precision; Wassersug, 1989;Hoff & Wassersug, 2000;Van Buskirk & McCollum, 2000;Larson & Reilly, 2003;Mcnamara et al, 2009;Aguayo et al, 2009;Johnson, Saenz, Adams, & Hibbitts, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, individuals could display larger and rounded mouth, more propulsion and/or maneuverability but lower endurance (dorso-ventral flexion) along the increasing of PC1 values. PC2 was principally driven by functional traits related to locomotion, indicated that with increased PC2 values, individuals were more compact and rounded, but less propulsion and/or maneuverability (i.e., lower movement precision; Wassersug, 1989;Hoff & Wassersug, 2000;Van Buskirk & McCollum, 2000;Larson & Reilly, 2003;Mcnamara et al, 2009;Aguayo et al, 2009;Johnson, Saenz, Adams, & Hibbitts, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The tail of tadpoles may show significant polyphenism, being able to change shape or color quickly in response to environmental modifications (Hoff & Wassersug, 2000). Such phenotypic plasticity allows the tail length to increase in response to stressful factors such as predators (Johnson, Saenz, Adams, & Hibbitts, 2015;McCollum & Leimberger, 1997;Van Buskirk & McCollum, 2000). The hydric stress applied in the present study, however, caused an inverse effect, reducing the tail length in tadpoles of both L. fuscus and P. nattereri, when compared with tadpoles that had not suffered any hydric stress ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…short periods of rapid movements), mean distance covered during bursts, maximum duration of bursts, maximum distance covered during bursts and maximum velocity (in mm/frame; Table S2). Because none of the measured traits were a priori expected to be of special relevance (for instance, aeshnid predators do not induce higher maximum velocity in amphibian larvae; Van Buskirk & McCollum, ; Gvoždík & Smolinský, ; Johnson et al ., ), we used a principal component analysis (PCA) on all seven positively correlated variables (pairwise correlations [ r s ] ranged from 0.37 to 0.91) to calculate overall locomotor activity of the larvae. Prior to PCA, the first six measures, characterized by right‐skewed distributions, were log‐transformed to reduce the influence of extreme values and to ensure that variables are linearly, or at least monotonically, related to one another (Quinn & Keough, ).…”
Section: Methodsmentioning
confidence: 99%